Peer review and accreditation in cardiac electrophysiology - Millar, R. Scott (SA Heart Journal, 2017)
In line with the world-wide trend towards peer review and audit in all branches of medical practice,the Cardiac Arrhythmia Society of South Africa (CASSA) has begun a process of voluntary accreditation of Cardiac Electrophysiologists, beginning with those members of the Executive Committee of CASSA in active EP practice. The immediate aim is to provide other practitioners, the public and funders with a list of electrophysiologists who meet agreed standards of experience and competence. The longterm goal is the registration of Cardiac Electrophysiology as a sub-speciality of Cardiology